2011
DOI: 10.1016/j.bbalip.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen upregulates hepatic apolipoprotein M expression via the estrogen receptor

Abstract: Apolipoprotein M (apoM) is present predominantly in high-density lipoprotein (HDL) in human plasma, thus possibly involved in the regulation of HDL metabolism and the process of atherosclerosis. Although estrogen replacement therapy increases serum levels of apoAI and HDL, it does not seem to reduce the cardiovascular risk in postmenopausal women. Therefore, we investigated the effects of estrogen on apoM expression in vitro and in vivo. HepG2 cells were incubated with different concentrations of estrogen w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 27 publications
0
9
1
Order By: Relevance
“…Although in the present study the levels of leptin were not measured, the reduced leptin levels might have happened as a reduction mechanism of Apo-M. However, the study reported that estrogen in vivo and in vitro conditions by a series of mechanisms upregulated the Apo-M (Wei et al, 2011). In this study, one of the possible reasons for low levels of Apo-M may be the decreased estrogen levels; So, the reduction of Apo-M in exercise and milk consumption group may be associated with estradiol further reduction.…”
Section: Resultscontrasting
confidence: 54%
“…Although in the present study the levels of leptin were not measured, the reduced leptin levels might have happened as a reduction mechanism of Apo-M. However, the study reported that estrogen in vivo and in vitro conditions by a series of mechanisms upregulated the Apo-M (Wei et al, 2011). In this study, one of the possible reasons for low levels of Apo-M may be the decreased estrogen levels; So, the reduction of Apo-M in exercise and milk consumption group may be associated with estradiol further reduction.…”
Section: Resultscontrasting
confidence: 54%
“…This observation does not prove a link between apoM and menopause, but the study supports the notion that apoM concentrations could be dependent on hormone levels, as the positive correlation with age is seen for women only. Few studies have addressed the effect of sex hormones on apoM, but it has been shown that estrogen upregulates apoM expression in vitro and in vivo in rats (44). This suggests that plasma apoM concentrations should be higher in pre-than postmenopausal women, which was not the case in the present study.…”
Section: Discussionmentioning
confidence: 54%
“…Estrogen up-regulates ApoE gene expression by increasing ApoE mRNA in the translating pool via the estrogen receptor alpha-mediated pathway (53). Estrogen up-regulates ApoM gene expression via the estrogen receptor in HepG2 cells (54). No previous studies have examined the effect of estrogen on the expression of the ApoD, ApoF, and ApoH genes.…”
Section: Discussionmentioning
confidence: 99%